Odpowiedzi

  • Użytkownik Zadane
2009-09-20T13:46:02+02:00
W=(-3,2) , przecinającą oś y (0,-1)
y=ax+b
2=-3a+b
-b=-3a-2
b=3a+2

y=ax+b
y (0,-1)
-1=b

podstawiam:
b=3a+2
-1=3a+2
-3a=2+1
-3a=3//:(-3)
a=-1

a=-1
b=-1

y=ax+b
podstawiam a i b
y=-x-1
2009-09-20T14:44:49+02:00
W = (-3,2) przecinającą oś y (0,-1)
y = ax + b
2 =-3a + b
-b =-3a - 2
b =3 a + 2

y = ax + b
y (0,-1)
-1 = b

podstawiam:
b = 3a + 2
-1 = 3a + 2
-3a = 2 + 1
-3a = 3 /: (-3)
a = -1

a = -1
b = -1

y = ax + b
podstawiam a i b
y = -x - 1